Canopy mortality has doubled in Europe's temperate forests over the last three decades. Issue 1 (December 2018) - Senf, Cornelius; Pflugmacher, Dirk; Zhiqiang, Yang; Sebald, Julius; Knorn, Jan; Neumann, Mathias; Hostert, Patrick; Seidl, Rupert
Abstract Mortality is a key indicator of forest health, and increasing mortality can serve as bellwether for the impacts of global change on forest ecosystems. Here we analyze trends in forest canopy mortality between 1984 and 2016 over more than 30 Mill. ha of temperate forests in Europe, based on a unique dataset of 24, 000 visually interpreted spectral trajectories from the Landsat archive. On average, 0.79% of the forest area was affected by natural or human-induced mortality annually. Canopy mortality increased by +2.40% year–1, doubling the forest area affected by mortality since 1984. Areas experiencing low-severity mortality increased more strongly than areas affected by stand-replacing mortality events. Changes in climate and land-use are likely causes of large-scale forest mortality increase. Our findings reveal profound changes in recent forest dynamics with important implications for carbon storage and biodiversity conservation, highlighting the importance of improved monitoring of forest mortality. Increases in tree mortality can signal changes in forest health, but large-scale tree mortality is difficult to quantify. Here Senf et al. show large-scale increases in forest mortality in Central Europe over the past 30 years, which were related to increasing growing stocks and temperature.